Evaluation of Surface Soils Contamination by Polycyclic Aromatic Hydrocarbons of Selected Samples in Al-Diwaniya City, Iraq - Faiq F. Karam (Journal of Global Pharma Technology, 2017)
The concentrations and spatial distribution of thirteen polycyclic aromatic hydrocarbons from٦ soil have been investigated in four regions locate in Al-Diwaniya city, Iraq. Sechelt extractions is used to extract PAHs compounds from all samples, gas chromatography was used to determine the PAHs concentration in all samples. The total concentrations of thirteen PAHs were ranged from 4.46ng.g-1 in site one to 17.24 ng.g-1 in site three of dry weight. The PAHs compounds those consist of four to six fused aromatic rings represent the majority among other PAHs in soil samples.Keywords: Al-Diwaniyah pollution, Contamination with PAHs, Extraction of PAHs from soil, Soil pollution, PAHs in Iraqi soil.